Resistin , Insulin resistance and BMI in type 2 diabetes mellitus and healthy subjects. - Al-Shamma, Zainab A.; Al-Yassin, Hedef D.; Hashim, Hashim M. (Journal of the Faculty of Medicine Baghdad, 2008)
Background : Obesity and insulin resistance have been quite well recognized as fundamental and leading causes of major health issues such as diabetes, hyperlipidemia, hypertension, and cardiovascular diseases. Abdominal obesity, particularly visceral adiposity is considered to play a major role in causing insulin resistance and type 2 diabetes mellitus , T2DM The resistin is considered one of the causes of insulin resistance which lead to hyperinsulinemia and a decrease in the quantitative insulin sensitivity check index (Quicki) which has been recently reported to be a useful marker of insulin resistance in patients with T2DM. Objective : The aim of the present study is to find the relationship between resistin and obesity as modulated by T2DM. Subjects and methods : The study involved 50 patients with T2DM with age range of 30 -70 years , and 30 healthy subjects ( control group ) of matching age and sex. Ten mLs of blood were collected from each patient and normal control subject after an overnight fast . One mL. was kept in an EDTA tube for mesureement of glycated Hb ( HbA1c) and the rest was allowed to clot , centrifuged and serum was divided into aliquots . Some was kept at (- 20 oC ) for measurement of resistin and insulin ( by enzyme linked immunosorbant assay , ELISA) and the rest for measurement of glucose , urea and creatinine ( by the available routine laboratory tests ) at the same day of collection. Results showed a significant rise in serum resistin in the obese diabetic patients as compared to the non obese patients. There are significant correlations between resistin and each of insulin resistance ( Quicki ) and degree of obesity (BMI) . Conclusion : Resistin & insulin resistance are significantly affected by BMI in diabetic patients only and not in the control group which implies that the obese control subjects didn’t have insulin resistances enough to show any change in resistin level. This confirms the synergistic effect of the obesity and diabetes on resistin level, while no effect of the disease per se could be detected from the present study.